Microstructure and Mechanical Properties of the Butt Joint in High Density Polyethylene Pipe - Pashupati Pokharel; Yoonsang Kim; Sunwoong Choi (International Journal of Polymer Science)
The microstructure and mechanical properties of the butt joint in high density polyethylene (HDPE) pipes were evaluated by preparing the joints with increasing the cooling time from 10 s to 70 s before pressure created for fusion of the pipes. Here, cold fusion flaws in HDPE butt joint were created with increasing the cooling time around 70 s caused by the close molecular contact followed by insufficient interdiffusion of chain segments back and forth across the wetted interface. The tensile failure mechanism of the welded pipes at different fusion time was projected based on the tensile test of dog-bone shaped, fully notched bar type as well as round U-notched specimens. The mechanical properties of the joints at different fusion time were correlated with the corresponding fracture surface morphology. The weld seam as well as tensile fracture surfaces were etched using strong oxidizing agents. The crystallinity of surface etched weld zone by potassium permanganate based etchant was found higher than unetched sample due to the higher susceptibility of amorphous phase of polyethylene with oxidizing agent. The U-notched tensile test of butt welded HDPE pipe and surface etching of the weldments provided clear delineation about the joint quality.